Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/biom11091368
|View full text |Cite
|
Sign up to set email alerts
|

Further Findings Concerning Endothelial Damage in COVID-19 Patients

Abstract: Systemic vascular damage with micro/macro-thrombosis is a typical feature of severe COVID-19. However, the pathogenesis of this damage and its predictive biomarkers remain poorly defined. For this reason, in this study, serum monocyte chemotactic protein (MCP)-2 and P- and E-selectin levels were analyzed in 204 patients with COVID-19. Serum MCP-2 and P-selectin were significantly higher in hospitalized patients compared with asymptomatic patients. Furthermore, MCP-2 increased with the WHO stage in hospitalized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 40 publications
1
11
0
Order By: Relevance
“…Neutrophils transiently increased at 2 dpi, and PTPRC + B cells increased at 2 and 5 dpi and then decreased at 7 dpi (Figure 3C; Supplementary Figure 4). The neutrophil-to-lymphocyte (NTL) ratio is crucial for prognosis and mortality in patients with COVID-19 (29)(30)(31)(32)(33)(34)(35); thus, we hypothesised that the composition of peripheral blood leucocytes would also vary in the SARS-CoV-2 infection mouse models. CBC analysis showed that the NTL ratio significantly increased to 7.34%, 20.64%, 11.94%, and 25.01% at 1, 2, 5, and 7 dpi, respectively, in K18-hACE2 mice (Figure 3D).…”
Section: Sars-cov-2 Infection Is Lethal In K18-hace2 Mice But Not In ...mentioning
confidence: 99%
“…Neutrophils transiently increased at 2 dpi, and PTPRC + B cells increased at 2 and 5 dpi and then decreased at 7 dpi (Figure 3C; Supplementary Figure 4). The neutrophil-to-lymphocyte (NTL) ratio is crucial for prognosis and mortality in patients with COVID-19 (29)(30)(31)(32)(33)(34)(35); thus, we hypothesised that the composition of peripheral blood leucocytes would also vary in the SARS-CoV-2 infection mouse models. CBC analysis showed that the NTL ratio significantly increased to 7.34%, 20.64%, 11.94%, and 25.01% at 1, 2, 5, and 7 dpi, respectively, in K18-hACE2 mice (Figure 3D).…”
Section: Sars-cov-2 Infection Is Lethal In K18-hace2 Mice But Not In ...mentioning
confidence: 99%
“…The authors believe that this confirms the importance of endothelial activation in the VTE mechanism in this disease (Fenyves et al, 2021). However, other authors believe (Gelzo et al, 2021) that endothelial damage is less relevant, since the level of E-selectin did not change, in contrast to platelet P-selectin. However, as the experience of many researchers shows, in most patients, along with coagulopathy, endotheliopathy is observed, and there is a need to strictly monitor the blood coagulation parameters of patients with varying degrees of COVID-19.…”
Section: P-selectin Is An Early Biomarker Of Thrombotic Complicationsmentioning
confidence: 56%
“…For instance neutrophil/lymphocyte ratio was been associated with disease severity with the original SARS-COV-2 variant due to significant reduction in lymphocytes and increase of neutrophils in patients with severe COVID during this phase of the pandemic. However this has not been replicated with subsequent waves and counts of neutrophils and lymphocytes may not change significantly between different severity groups [18]. There are some limitations to our report.…”
Section: Plos Onementioning
confidence: 60%